Saint Gerald of Braga and the fruits of devotion - Carvalho, Luis; Fernandes, Francisca Maria; Nozes, Paula; Figueira, Ana Paula; Nunes, Maria de Fátima (Ethnobotany Research and Applications, 2025)
The Cathedral of Braga, one of Portugal’s most iconic religious landmarks, preserves a profound connection between sacred traditions and fertility symbolism. At the core of this association stands Saint Gerald, whose legend recounts a remarkable event—fruits miraculously ripening in the depths of late autumn. This episode gave rise to a lasting ritual: each year, during his feast, his chapel is adorned with fruit, echoing ancient fertility symbols rooted in the same location, where a Roman temple once stood in honor of the Egyptian goddess Isis. Revered as a divine mother and guardian of life, Isis shares striking iconographic parallels with the Christian Virgin of Milk, reinforcing themes of abundance and motherhood. The fruit offerings in Saint Gerald’s chapel thus serve as a bridge between pagan and Christian fertility motifs, illustrating the seamless continuity of sacred traditions. Still observed in modern-day Braga, this enduring practice not only sustains religious devotion but also highlights the historical interplay of fertility, divine intercession, and cultural identity, all symbolized through the offering of fruit. Keywords: Saint Gerald of Braga, fruits and fertility, plants in Christian traditions, cult of Isis, Virgin of Milk.